The territories of the People's Republic of China - Boland-Crewe, Tara.; Lea, David, 1972- (London ; New York : Europa, 2002)
Provides up-to-date and impartial information that helps give an understanding of the regional dimension of the country as well place it in economic, political and historical contexts.
Book Cover; Title; Economic Regionalism in the People's Republic of China; Governing China: Unity, Control, Decentralization and Global Integration; Chronology of the People's Republic of China; Statistics; The Government of the People's Republic of China; Anhui; Fujian; Gansu; Guangdong; Guizhou; Hainan; Hebei; Heilongjiang; Henan; Hubei; Hunan; Jiangsu; Jiangxi; Jilin; Liaoning; Qinghai; Shaanxi; Shandong; Shanxi; Sichuan; Yunnan; Zhejiang; Guangxi; Nei Mongol; Ningxia; Xinjiang; Xizang (Tibet); Beijing; Chongqing; Shanghai; Tianjin; Hong Kong; Macao; Index of Alternative Names.
Includes indexes.
Print version record.
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: China -- Territories and possessions; HISTORY; Chinese territories and possessions